2020
DOI: 10.3390/v12030291
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Mid-Gestation Pregnant Female and Intact Male Sheep with Zika Virus

Abstract: Zika virus (ZIKV) is an arbovirus that causes birth defects, persistent male infection, and sexual transmission in humans. The purpose of this study was to continue the development of an ovine ZIKV infection model; thus, two experiments were undertaken. In the first experiment, we built on previous pregnant sheep experiments by developing a mid-gestation model of ZIKV infection. Four pregnant sheep were challenged with ZIKV at 57-64 days gestation; two animals served as controls. After 13-15 days (correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
(130 reference statements)
5
2
1
Order By: Relevance
“…In this study, the EBs from co-cultures had lower viral loads as compared to the placental cell lines. This supports reports of ZIKV titers in fetal and placental tissues in vivo [ 28 , 65 , 66 ]. Since macrophages or other monocytes were not used in this study, the enhancement we observed was likely due to antibody-mediated enhancement (AME).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the EBs from co-cultures had lower viral loads as compared to the placental cell lines. This supports reports of ZIKV titers in fetal and placental tissues in vivo [ 28 , 65 , 66 ]. Since macrophages or other monocytes were not used in this study, the enhancement we observed was likely due to antibody-mediated enhancement (AME).…”
Section: Discussionsupporting
confidence: 92%
“…The data in this study show that within 72 h p.i., ZIKV effectively crosses two monolayers, a basement membrane, and infects an EB. The detection of ZIKV in cells located on each side of the membrane as a model for the maternal–fetal axis supports reports of the isolation of ZIKV from placentas and fetuses [ 28 , 50 , 65 , 66 ]. However, the permissiveness of the cells observed in this study may not reflect the cellular tropism of ZIKV in actual placentas [ 67 , 68 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, EBs had enhanced ZIKV infection along with lower viral loads as compared to the placental cell lines. This supports reports of ZIKV titers in fetal and placental tissues in vivo [28,68,69]. Since macrophages or other monocytes were not used in this study, the enhancement we observed was likely due to antibody mediated enhancement (AME).…”
Section: Discussionsupporting
confidence: 90%
“…ZIKV infection during the first trimester also causes placental pathology, fetal growth restriction, and fetal loss [ 42 ]. Infection of pregnant sheep (gestational day 57 to 64) with a high dose of ZIKV (strain R103451, 10 8 PFU) via the intravenous and subcutaneous route results in detectable infectious virus in the maternal spleen, placenta, and fetal organs including brain, spleen, and liver, with fetuses exhibiting significantly smaller head sizes as well as gross pathology following euthanasia by 15 dpi [ 43 ]. Taken together, these findings suggest that pregnant sheep are a useful large animal model to study ZIKV pathogenesis in the context of CZS.…”
Section: Methodsmentioning
confidence: 99%